Living the intensive order: Common sense and schizophrenia in Deleuze and Guattari - Wielen-Honinckx, Julie van der (Nursing philosophy, 2018)
In Anti-Oedipus, Deleuze and Guattari aim to describe schizophrenia in a positive manner. According to them, the schizophrenic lives on the intensive order. To fully comprehend what this means, it is key to address some of Deleuze's insights regarding the notion of intensity in relation to experience and cognition. This is why I will combine ideas from Anti-Oedipus with theory from Difference and Repetition, in order to explain Deleuze and Guattari's conception of intensity in its relation to common sense and to schizophrenia. According to this conception (a), intensity is the condition of possibility and limit for the sensible; (b) it becomes covered over by the organizing principles of common sense, which make our affects more workable and recognizable; and (c) this process of organization must hang together with the codification of desire through Oedipus, the main organizational principle of the socius. On the back of these theoretical considerations, I will explain what it means to say that the schizophrenic lives amongst intensities: (a) this involves a lack of codification of desire and thus of common sense, meaning an absence of organizational principles; and (b) this perspective leads to a different understanding of the schizophrenic's experience and expression, with very concrete implications for a clinical approach to schizophrenia.